A Rare Case of Takayasu Arteritis Presenting as Pericarditis with Effusion - Ian J. Robertson; David K. Mecham; Lisa M. Conte; Michael F. Loncharich (Case Reports in Rheumatology)
Takayasu arteritis (TAK) is a rare large-vessel vasculitis that is seen primarily in young females of Asian descent and is infrequently diagnosed in the United States. Pericardial effusion with or without pericarditis as a presenting feature of TAK is rare, with only about five percent of cases of pericarditis attributable to any autoimmune etiology. We present a case of a 22-year-old Caucasian woman who presented with a large, symptomatic pericardial effusion of unclear etiology, who after extensive laboratory workup and imaging to include whole-body positron emission tomography (PET) was diagnosed with TAK. In our patient, the use of whole-body PET showing characteristic hypermetabolism within the aortic arch helped secure our diagnosis while avoiding the need for pericardiocentesis. The patient had rapid symptomatic and radiographic improvement with the use of high-dose oral steroids in addition to colchicine and ibuprofen for her pericarditis and associated pericardial effusion. At follow-up just 1 week after initiation of steroids, only trace effusion was identified on transthoracic echocardiogram.